Teknik Permainan Mangenet pada Instrumen Tradisional Sulim Batak Toba dalam Mengiringi Lagu BE.683 di AdopanMu Jesus di Gereja HKBP Bahalbatu I. - G. A. Ebenezer L. Toruan; Eben Haezarni Telaumbanua; Testi Bazarni Zebua; Roy J. M. Hutagalung; Aprinaldi P Simorangkir (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
The purpose of this research is to find out game techniques mangenet on the traditional Sulim Batak Toba instrument to accompany the song BE.683 "Di AdopanMu Jesus" at HKBP Bahalbatu I. Sulim is a traditional Batak Toba musical instrument, Sulim is made from bamboo, the Sulim instrument is blown from the side or is called a side blown flute. The Sulim instrument has been widely used in church services, especially in the HKBP Bahalbati I church. The Sulim instrument has been used to accompany worship services. especially in accompanying the song from BE .683 "In Your Adopan Jesus. This song is played at a larghetto tempo with a tempo of 65 BPM. This song was created by Hugo Nyberg in 1873 with the title "For jesus milda ogon" which was later translated into Toba Batak language by Rev. J.A.U. Doloksaribu and Rev. MV. Simajuntak. Meanwhile, the technique used in performing this song is the mangenet technique with the Sulim Batak Toba instrument. In this technique, the researcher combines the trial, slur, crescendo, descrecendo techniques to produce the mangenet playing technique on the sulim instrument and then the author combines this technique with the ambush or blowing technique, breathing technique, fingering technique and holding the sulim instrument.